Pengaruh Model Pembelajaran Inkuiri Berbantuan Laboratorium Virtual Terhadap Penguasaan Konsep Fisika Peserta Didik - Mahesti Kusdiastuti; Ahmad Harjono; Hairunnisyah Sahidu; Gunawan Gunawan (Department of Physics Education, Universitas Mataram, 2016)
This study aims to determine the effect model of inquiry aided virtual laboratory to physical concept comprehension of students MA DI Putri Nurul Hakim Kediri the academic year 2015/2016. Experimental research design using